(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: In recent years, the travel and tourism industry has experienced significant growth, with an increasing number of tourists exploring different destinations for leisure, business, and other purposes. This surge in travel has led to a parallel expansion in the accommodation sector, with a diverse array of options available to cater to the evolving needs and preferences of travelers. Consequently, it has become imperative for accommodation providers to understand the factors that influence consumers’ choices. Objective: To identify and find relationship between the preferred type of accommodation and gender. Another aim of the study was to identify and find relationship between the factors of choosing accommodation and gender. Methodology: Research design was descriptive. Study was conducted in Delhi- NCR. The tool used for survey was close ended questionnaire. A sample size of 100 was chosen randomly using convenience method. The majority of the respondents were in the age group of 18-30 years. The data has been analyzed on the basis of gender and the statistical analysis was done using MINITAB 14 and chi square test. Results: 54% of the guests who mostly come from the age group of 18-30 years and prefer traditional accommodation i.e., hotel as compared to other accommodation alternatives and for 45% of them price is the most important factor while location with 41% of the total response being the second while choosing their accommodation. The association between gender and vacation rental (homestay) was found to be significant and for rest of the accommodation type the association was not significant. Similarly, the association between gender and location as factor for choosing accommodation was significant. Conclusion: From the present study we may conclude that location and homestays are the preferred choice of both the genders.